2004
DOI: 10.3748/wjg.v10.i9.1375
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of doxorubicin induced heat shock protein 72 on cold preservation injury of rat livers

Abstract: AIM:To observe the protective effect of heat shock protein 72 (HSP 72) induced by pretreatment of doxorubicin (DXR) on long-term cold preservation injury of rat livers. METHODS:Sprague-Dawley rats were administered intravenously DXR at a dose of 1 mg/kg body mass in DXR group and saline in control group. After 48 h, the rat liver was perfused with cold Linger's and University of Wisconsin (UW) solutions and then was preserved in UW solution at 4 for 24, 36 and 48 h. AST, ALT, LDH and hyaluronic acid in preserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Data represented in Table (1) revealed that activities of serum AST, ALT were markedly elevated in doxorubicin treated groups compared to control group, indicating liver injury. The present results are in agreement with many authors as (Chen et al, 2004) who reported that, doxorubicin treated rats induce significant increases in ALT, AST and bilirubin serum levels when compared with the untreated control group.…”
Section: Discussionsupporting
confidence: 94%
“…Data represented in Table (1) revealed that activities of serum AST, ALT were markedly elevated in doxorubicin treated groups compared to control group, indicating liver injury. The present results are in agreement with many authors as (Chen et al, 2004) who reported that, doxorubicin treated rats induce significant increases in ALT, AST and bilirubin serum levels when compared with the untreated control group.…”
Section: Discussionsupporting
confidence: 94%
“…But it is still unclear what pathways are involved in the cytokine reduction. One possibility is that the protection of hepatocytes and sinusoidal endothelial cells by Hsp72 prevents microcirculatory failure and, subsequently, the immune cell accumulation [1,33]. However, we cannot rule out the possibility that HS þ MES might have some direct function of suppressing the cytokine expressions.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, investigators in several studies (15)(16)(17)(18) have demonstrated complementary interactions when they combined RF ablation and concurrent administration of the chemotherapeutic agent doxorubicin, particularly in the form of a liposomal preparation. Researchers in mechanistic studies (19)(20)(21) have further shown that liposomal doxorubicin increases effectiveness of ablation, in part by cellular stress leading to apoptosis, but also produces heat-shock proteins (HSPs), such as 70-kDa HSP (HSP70), which have been shown to limit tissue damage. Therefore, other compounds that have greater apoptosis potential and/or HSP suppression hold the potential to further increase RF ablation-induced tissue coagulation.…”
Section: Experimental Studies: Increasing Tumor Coagulation and Survimentioning
confidence: 99%